Model Dinamika Sistem Pasokan dan Distribusi pada Gangguan Pendistribusian BBM PT. Pertamina Padang - Ivan (Jurnal Optimasi Sistem Industri, 2012)
This paper discusses supply and distribution Bahan Bakar Minyak (BBM) system at PERTAMINA Padang to look a performancy system that disturbance of distribution like replacement Automatic Circuit Breaker (ACB). The replacement of ACB processes about 12 hours and causes the distributing activity of BBM to Stasiun Pengisian Bahan Bakar Umum (SPBU) has to be stopped. It makes impact toward the work ability of supplying and distributing system. Therefore, a planning model which is able to see the impact of ACB replacement toward system behavior of supplying and distributing is needed. Purpose of the modelling is to study the behavioral effects of variable in supply and distribution system using causal loop diagram and stock flow diagram. Result of this diagram has built simulation model to analyze performance system. Verification testing done by the method of checking the level and flow and testing of the coding. Validation of the model while the testing is done by operational graphics and the variability parameter sensitivity analysis. The model was designed and carried out the design of simulated scenarios to determine a strategy for decision-makers to look at the performance of BBM supply and distribution system.